Detection and attribution of changes in 20th century land precipitation - Lambert, F; Stott, P; Allen, M; Palmer, M (2004)
Observed globally-averaged land precipitation changes over the 20th century are compared with simulations of the HadCM3 climate model using an "optimal fingerprinting" method. We find that observed changes in precipitation are too large to be consistent with model-generated internal variability and are consistent with (attributable to) the combination of natural and anthropogenic forcings applied to the model. By comparing precipitation observations to shortwave and longwave forcing timeseries, we find that most of the forced variation in precipitation appears to be driven by natural shortwave forcings. We are unable to detect a response to anthropogenic longwave forcings in isolation. Finally, we seek to explain these results in terms of perturbations to the energy budget of the troposphere. Copyright 2004 by the American Geophysical Union.